Effect of Nutrients on the Growth Behaviour of Bambusa tulda in the Nursery - Raina, A. K.; Prasad, K. G.; Pharasi, S. C.; Kapoor, K. S.; Singh, S. B. (Indian Forester, 1988)
An experiment comprising 3 levels of nitrogen (0, 50 and 100 ppm) 3 levels of P2O5, (0, 50 and 100 ppm) and 7 application dates of each, was conducted in nursery to see tbeir effect on some important growth parameters (plant height, tiller and leaf number, Collar diameter and biomass production) of Bambusa Tulda.biomass production) of Bambusa tulda. Results recorded arter 17 weeks of germination revealed that for all growth parameters, separate application of nitrogen was superior than phosphorus application but their combined applications were always better than individual application. Among the doses, N100P50 was found best. Split applications of nutrients 4, 6 and 8 weeks after germination gave best results.